ANALISIS KESESUAIAN TEKS VERBAL DAN VISUAL PADA BUKU TEKS BAHASA INDONESIA KELAS X PENERBIT KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN RI EDISI REVISI 2017 - Muhamad Irwan Saputra (Universitas Negeri Medan, 2019)
ABSTRACT This study aims to describe the analysis of verbal and visual text in the books of class X students at SMA Negeri 1 Secanggang and measure the level of students' understanding of verbal and visual texts and their analysis. This study uses qualitative interpretatif and quantitative data. The study was taken by interview, observation and questionnaire. From the results of the analysis, it can be seen that, (1) Halliday's transitivity concept analysis shows the verbal text on the process type component the number of occurrences of verbal text 11 times, on the participant component the number of appearances on verbal text is 11 times, and on the circumstance component the number of appearances on verbal text is 8 times. (2) Analysis of visual text in class X students' books using a multimodal analysis model by Kres s and Van Leeuwen which includes linguistic, visual, audio, gestural, and location analysis . (3) Analysis of the suitability of verbal and visual texts shows that the highest amount of conformity is in the display text of the exposition of